2021
DOI: 10.3390/ijerph18157730
|View full text |Cite
|
Sign up to set email alerts
|

How Is Work Ability Shaped in Groups of Shift and Non-Shift Workers? A Comprehensive Approach to Job Resources and Mediation Role of Emotions at Work

Abstract: There is much less research on the relationship between shift work and positive states experienced in the workplace, e.g., emotions and work ability. Using the job demands-resources model, conservation of resources theory and the broaden-and-build theory as theoretical frameworks, the direct and indirect (mediated via positive and negative emotions) relations between the complex of job resources and work ability were tested in the group of shift and non-shift workers. Three types of resources related to task, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 112 publications
0
2
0
Order By: Relevance
“…Positive affect at work, understood as a subjective emotional assessment of work, may be conditioned, among other things, by the level of social support at work. Earlier research confirmed the positive relationship between institutional support and a positive emotional response towards work (Moreira‐Fontán et al, 2019), and the positive relationship between resources and positive affect at work as well as work ability (Baka et al, 2021).…”
Section: Introductionmentioning
confidence: 69%
“…Positive affect at work, understood as a subjective emotional assessment of work, may be conditioned, among other things, by the level of social support at work. Earlier research confirmed the positive relationship between institutional support and a positive emotional response towards work (Moreira‐Fontán et al, 2019), and the positive relationship between resources and positive affect at work as well as work ability (Baka et al, 2021).…”
Section: Introductionmentioning
confidence: 69%
“…Willett et al (2023) found a correlation between communication and leadership. Baka et al (2021) show that with good leadership, there will be an increase in different work abilities between non-shift and shift employees. These findings imply a correlation or relationship between resilient leadership and work ability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Work ability is an element of the safety culture of the workplace and is treated as an important factor contributing to safer work which does not threaten the health and life of employees. Numerous studies on antecedents of work ability show that it correlates with higher age, harmful working conditions, and shift work [11,12], as well as prolonged job demands [13][14][15] and insufficient job resources [16][17][18][19]. For example, a systematic review by van den Berg et al [15] showed that both high job demands (related to physi cal and psychological demands) and low job resources (related to low levels of autonomy and poor ergonomic conditions) correlate with low work ability.…”
Section: Burnout and Work Abilitymentioning
confidence: 99%